Observation of new resonances in the [lambda]0bπ+π- system - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; Comerma-Montells, Albert; D'Argent, Philippe; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; et al. (Physical review letters, 2019)
We report the observation of a new structure in the Λ0bπ+π− spectrum using the full LHCb data set of pp collisions, corresponding to an integrated luminosity of 9 fb−1, collected at √s=7, 8, and 13 TeV. A study of the structure suggests its interpretation as a superposition of two almost degenerate narrow states. The masses and widths of these states are measured to be mΛb(6146)0=6146.17±0.33±0.22±0.16 MeV,mΛb(6152)0=6152.51±0.26±0.22±0.16 MeV,ΓΛb(6146)0=2.9±1.3±0.3 MeV,ΓΛb(6152)0=2.1±0.8±0.3 MeV,with a mass splitting of Δm=6.34±0.32±0.02 MeV, where the first uncertainty is statistical, the second systematic. The third uncertainty for the mass measurements derives from the knowledge of the mass of the Λ0b baryon. The measured masses and widths of these new excited states suggest their possible interpretation as a doublet of Λb(1D)0 states.